Keys for designing hematite/plasmonic metal hybrid nanostructures with enhanced photoactive properties - Encina, Ezequiel Roberto (2018)
Photoactive hybrid nanostructures composed of metal oxides and plasmonic metals are able to perform the conversion of radiant (solar) energy into electrical or chemical energy. However, their use in large-scale practical applications still requires their photoconversion efficiency to be improved. In this work, the light-harvesting properties of hematite/plasmonic metal rodlike hybrid nanostructures are investigated on the basis of discrete dipole approximation simulations. The effects of the length and nature of the metallic counterpart on the far- and near-field optical properties of the hybrid nanostructure are analyzed in detail. The implemented methodology allowed us to assess the contribution of each component of the hybrid nanostructure to the absorption efficiency, Qabs, separately. In turn, the Qabs values obtained were employed to determine the absorbed photon flux, ø, within the α-Fe2O3 component, a relevant quantity directly related to the photoconversion efficiency. It was found that both absorption efficiency Qabs and absorbed photon flux ø can be largely enhanced through a proper selection of the length and nature of the metallic counterpart of the nanostructure, evidencing plasmon-enhanced light absorption in the α-Fe2O3 component, which is attributed to a plasmon-induced energy transfer mechanism based on near-field enhancements. Importantly, it was found that the highest ø values achieved for nanostructures composed of Ag and Al (∼11 × 1016 photons cm-2 s-1) are nearly 3 times larger than those corresponding to nanostructures composed of Au (∼4 × 1016 photons cm-2 s-1). In addition, a direct relationship between the absorbed photon flux, ø, and optical characteristics of the nanostructures, that is, the bandgap energy of α-Fe2O3 and the energy and radiative line width of the localized surface plasmon resonance, was empirically obtained. Such a relationship not only complements but also overcomes the limitations of the reported useful criteria and provides helpful guidelines for the optimum design of hybrid nanostructures with enhanced photoactive properties.